The Internalization of Sunan Drajat Social Concept in Multicultural Education Implementation - Zainuddin, Ammar; Nasucha, Juli Amaliya (Universitas Islam Negeri Raden Intan Lampung, 2018)
Multicultural education is a manifestation of the process of respecting diversity among others and accepting each other. The most basic thing about this education is to uphold human values so as to create a sense of justice, togetherness and a sense of inequality or discrimination. As an example and role model that needs to be observed is Drajat's attitude in preaching and teaching morality. He and the community were known to be very wise and more concerned with caring for others. Thus it can be seen in his advice which includes catur menehono. It's a pity if Sunan's teachings on human rights are used as a memory in history. Therefore, here the writer wants to study more in the meaning of chess menehono teachings Sunan Drajat and try to redesign how the social teachings are applied in the scope of education.